COLLECTION SECURITY MANAGEMENT AT UNIVERSITIES LIBRARIES: ASSESSMENT OF ITS IMPLEMENTATION STATUS - A. A., Maidabino; A.N., Zainab (Malaysian Journal of Library and Information Science, 2017)
This study examines the literature on library security and collection security to identify factors to be considered to develop a collection security management assessment instrument for universitylibraries. A “house” model was proposed consisting of five factors; collection security governance, operations and processes, people issues, physical and technical issues and the security culture in libraries. An assessment instrument listing items covering the five factors was pilot tested on 61 samples comprising chief librarians, deputy librarians, departmental, sectional heads and professional staff working in four university libraries in Nigeria. The level of security implementation is assessed on a scale of 1=not-implemented, 2=planning stage, 3=partial implementation, 4=close to completion, and 5=full implementation. The instrument was also tested for reliability. Reliability tests indicate that all five factors are reliable with Cronbach’s alpha values between 0.7 and 0.9, indicating that the instrument can be used for wider distribution to explore and assess the level of collection security implementation in university libraries from a holistic perspective.